Prevalence, Associated Factors, and Consequences of Burnout Among Egyptian Physicians During COVID-19 Pandemic - Abdelhafiz, Ahmed Samir; Ali, Asmaa; Ziady, Hany H.; Maaly, Ayman Mohamed; Alorabi, Mohamed; Sultan, Eman A. (Frontiers in Public Health, 2020)
Objectives: COVID-19 has been recognized as a pandemic by the World Health Organization, and physicians are at the frontline to confront the disease. Burnout syndrome (BOS) is a syndrome resulting from chronic workplace stress that has not been successfully managed. The objective of this study is to evaluate the frequency and associated risk factors of BOS among a sample of Egyptian physicians during the COVID-19 pandemic. Methods: Using Maslach Burnout Inventory Human Services Survey, a cross-sectional electronic survey was conducted to assess BOS among the target group. Results: Two hundred and twenty physicians participated in the study. The frequency of BOS among the research group was 36.36%. The possibility of development of BOS increased two times with the need to buy personal protective equipment (PPE) from participants' own money, with harassment by patients' families, and was less likely to develop in doctors with older age. While male gender was a predictor of depersonalization (DP), female gender showed a significant association with higher emotional exhaustion (EE). Infection or death from COVID-19 among colleagues or relatives showed significant association with elevated EE and lowered personal achievement (PA), respectively. Conclusion: COVID-19 pandemic added new factors to the development of BOS in our research group. Several measures should be taken to support physicians at this stage. These measures include psychological support, organizing work hours, adjusting salaries, and providing personal protective equipment and training on safety measures.